House dust fungal communities' characterization: A double take on the six by sixty by six (6 × 60 × 6) project - Amaro, R (2016)
Fungi are a group of microbes that are found with particular incidence in the indoor environment. Their direct toxicity or capability of generating toxic compounds has been associated with a large number of adverse health effects, such as infectious diseases and allergies. Given that in modern society people spend a large part of their time indoors; fungal communities' characterization of this environmental compartment assumes paramount importance in the comprehension of health effects. House dust is an easy to obtain, time-integrative matrix, being its use in epidemiological studies on human exposure to environmental contaminants highly recommended. Furthermore, dust can carry a great variety of fungal content that undergoes a large number of processes that modulate and further complexify human exposure. Our study aims to identify and quantify the fungal community on house dust samples collected using two different methodologies (an approach not often seen in the literature): active (vacuum cleaner bags) and passive sampling (dust settled in petri dishes). Sampling was performed as part of the ongoing 6 × 60 × 6 Project in which six houses from Covilhǎ (Portugal), with building dates representative of six decades, were studied for a period of sixty days. © 2016 Raquel Amaro et al. 2016.